The alterations of blood-testis barrier in experimental testicular ınjury models - ERCAN, FERİHA (My University, 2022)
The blood-testis barrier is found between the Sertoli cells and divides the seminiferous tubule epithelium into basal and adluminal compartments. The germinal cell renewal, differentiation and cell cycle progression up to the preleptotene spermotocytes stage take place in the basal compartment, however, meiosis, spermiogenesis and spermiation take place in the adluminal compertment. The blood-testis barrier consists of tight junctions as well as ectoplasmic specialisations, desmosomes and gap junctions to create specific microenvironment for the completion of spermatogenesis to form spermatozoa. The blood-testis barrier is not a static ultrastructure, it undergoes extensive restructuring during the seminiferous tubule epithelial cycle of spermatogenesis to allow the transit of preleptotene spermotocytes at the blood-testis barrier from basal compartment towards the adluminal compartment. The functions of the blood-testis barrier include preventing the transport of biomolecules into the paracellular space, forming an immunological barrier, separating cellular processes during the spermatogenic epithelial cycle, and establishing the cellular polarity of the seminiferous tubule. However, various environmental conditions, chemotherapeutic agents, toxic substances and lifestyle have degenerative effects on blood-testis barrier, resulting in testicular damage, altered sperm parameters and ultimately male infertility. The alterations in morphological and molecular organization of blood-testis barrier in different experimentally induced testis injury models arc reviewed in this article.
Keywords: Tıp; Histoloji-Embriyoloji; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Histology and Embryology; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Moleküler Biyoloji ve Genetik; TIP, GENEL & DAHİLİ; HÜCRE BİYOLOJİSİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; MOLECULAR BIOLOGY & GENETICS; MEDICINE, GENERAL & INTERNAL; CELL BIOLOGY; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Hücre Biyolojisi; Yaşam Bilimleri; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Cell Biology; Life Sciences; Blood-testis barrier; Sertoli cells; Tight junction; Testicular injury models; MORPHOLOGICAL ALTERATIONS; ELECTROMAGNETIC-WAVES; NITROSATIVE STRESS; MOBILE PHONES; PROTEINS; JUNCTION; PERMEABILITY; OCCLUDIN; Blood-testis barrier; Sertoli cells; Tight junction; Testicular injury models